Towards Open Annotation: Examples and Experiments - Seatter, Lindsey (KULA, 2019)
This article interrogates how digital text annotation tools and projects facilitate online engagement and virtual communities of practice. With the rise of the Web 2.0 movement and the proliferation of digital resources, annotation has evolved from an isolated practice to a collaborative one. This article unpacks the impact of this shift by providing an in-depth discussion of five web-based tools and two social reading projects. This article examines issues of design, usability, and applicability to pedagogical intervention as well as underscores how productive group dynamics can be fostered through digital, social annotation.